A Juridical Study of Constitutional Court Decision No. 58/PUU-VIII/2010 on the Right to Education and Non-Discrimination in Indonesia - Dewi, Sari Amalia; Uwiyono, Aloysius; Saleh, Rosdiana (Eastasouth Institute, 2025)
This study presents a normative juridical analysis of Constitutional Court Decision Number 58/PUU-VIII/2010, which addresses the constitutional right to education and the principle of non-discrimination in Indonesia. The decision represents a significant advancement in Indonesian constitutional jurisprudence, affirming the state’s obligation to ensure equal access to education as mandated by Article 31 of the 1945 Constitution. Using a normative legal approach, this study examines the Court’s reasoning, relevant constitutional provisions, and the decision’s broader implications for human rights and educational equity. The findings show that the Constitutional Court emphasized education as a fundamental and universal right, requiring the state to adopt affirmative measures to eliminate structural inequalities and discriminatory practices in educational policy. The decision aligns national law with international human rights instruments such as the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. Overall, this study concludes that Decision Number 58/PUU-VIII/2010 strengthens Indonesia’s constitutional framework for protecting the right to education and reinforces the state’s responsibility to promote equality, inclusivity, and social justice within the education system.